Analisis Hukum dan Prospek Pekerja Outsourcing untuk Diangkat sebagai Karyawan Tetap - Sheren Agapena Hosaya Liunda; Gunardi Lie (Universitas Sains dan Teknologi Komputer, 2024)
Work is an effort to survive for humans. In general, when someone works for someone else, there is a work bond that is formed, namely the relationship between employee and entrepreneur. Some companies' current use of outsourcing labor models is generally driven by the company's strategy to optimize production costs. Outsourced employees have a different work status from permanent employees at the company where they are placed. However, in some situations, especially if statutory regulations or agreements between the outsourcing company and the company where they are placed allow it, outsourced employees can be appointed as permanent employees. The above article was made using a normative juridical study type research method. The results of this research are that in several situations, especially if the statutory regulations or agreement between the outsourcing company and the company where they are placed allows it, outsourced employees can be appointed as permanent employees. So, to be appointed as permanent employees, outsourced employees need to meet the criteria contained in the placement company.